Asphyxia neonatorum in a developing world situation : a study of the impact of asphyxia neonatorum in term infants on the pattern of handicap in the Ciskei; an evalution of its epidemiology and a trial of the efficacy of current therapy - Power, David John Donovan (Department of Paediatrics and Child Health, 2018)
This study addresses the problem of asphyxia neonatorum in a developing African community in the Mdantsane region of Ciskei. It also documents asphyxia as a prominent cause of childhood handicap, examines aspects of its epidemiology and evaluates the effectiveness of a regimen of phenobarbitone and dexamethasone in limiting subsequent neurological deficit in asphyxiated neonates. Analysis of neonatal deaths at Cecilia Makiwane Hospital over an 18-month period showed that asphyxia accounted for one third of all neonatal deaths. In particular, asphyxia caused two thirds of deaths in infants over 2 Kg birth weight. From a hospital register of handicapped children, 211 had cerebral palsy. Asphyxia was the cause of cerebral palsy in 33% of these children. Spastic quadriplegia, the type of cerebral palsy most often resulting from the cerebral damage associated with asphyxial hypoxic-ischaemic insults, was by far the largest diagnostic category (57%). Asphyxia therefore appears to be the single largest cause of significant handicap in Ciskei. In view of the underdeveloped support services to parents in most developing areas, the problem of asphyxia is of considerable importance. In the study of the epidemiology of asphyxia, details of pregnancy and labour were obtained for 163 asphyxiated term infants and 2758 non- asphyxiated term infants whose mothers had delivered in the hospital. The factors positively associated with asphyxia were: low gravidity and parity, failure to book for antenatal care, the occurrence of antenatal disorders, the occurrence of fetal distress, a prolonged first stage of labour and delivery by caesarean section or vacuum extraction. Maternal age and the actual number of antenatal visits were not associated with asphyxia. The causes of asphyxia assigned by the specialist obstetrician in charge were cephalopelvic disproportion (CPD) (39%), utero-placental pathologies (22%), other (8%), and "unknown" where he could find no abnormality in pregnancy and labour (27%). From these findings it appears that the steps that need to be taken for prevention include: active recruitment of patients to book for antenatal care, more active detection and management of cephalopelvic disproportion and basic research to elucidate the causes of the "unknown" group whom it is speculated have undetected utero-placental pathology.